Safety and efficacy of CVT-301 (levodopa inhalation powder) on motor function during off periods in patients with Parkinson's disease: a randomised, double-blind, placebo-controlled phase 3 trial. Issue 2 (February 2019) - LeWitt, Peter A; Hauser, Robert A; Pahwa, Rajesh; Isaacson, Stuart H; Fernandez, Hubert H; Lew, Mark; Saint-Hilaire, Marie; Pourcher, Emmanuelle; Lopez-Manzanares, Lydia; Waters, Cheryl; Rudzínska, Monika; Sedkov, Alexander; et al.
Summary: Background: Patients with Parkinson's disease chronically treated with levodopa commonly have delayed or unpredictable onset of its benefits after oral intake. In this study, we assessed the safety and efficacy of CVT-301, a self-administered levodopa oral inhalation powder, for the treatment of patients with Parkinson's disease during off periods. Methods: In this randomised, double-blind, placebo-controlled, phase 3 trial, patients were recruited at 65 sites in Canada, Poland, Spain, and the USA. Eligible participants were patients with Parkinson's disease aged 30–85 years, who had daily off periods of 2 h or longer and showed an improvement of 25% or greater in the Unified Parkinson's Disease Rating Scale (UPDRS) motor score from off to on state after use of an oral levodopa plus a dopa-decarboxylase inhibitor combination. Patients were assigned (1:1:1) with a computer-generated randomisation code, in fixed blocks of six, to either CVT-301 60 mg, CVT-301 84 mg, or placebo. Spirometry results and modified Hoehn and Yahr disease stage at screening were used for stratification of treatment groups. Patients, the sponsor, and site personnel were masked to treatment assignment. Each study dose consisted of two capsules administered with an inhaler. Patients were instructed to use the study drug as needed for off periods, and could self-administer up to five doses per day. The primary endpoint was the change in UPDRS motor score from predose to 30 min postdose, assessed at week 12 during an in-clinic off period, in the CVT-301 84 mg group compared with the placebo group. Analysis was by intention to treat. Safety was assessed in all patients who received at least one dose of experimental treatment. This trial is registered withClinicalTrials.gov, numberNCT02240030 . Findings: Between Dec 4, 2014, and Aug 26, 2016, 351 patients were enrolled and randomly assigned to receive CVT-301 60 mg (115 patients), CVT-301 84 mg (120 patients), or placebo (116 patients). Of these, 339 received the assigned study treatment (CVT-301 60 mg, n=113; CVT-301 84 mg, n=114; placebo, n=112) and 290 completed the study (CVT-301 60 mg, n=96; CVT-301 84 mg, n=97; placebo, n=97). The least-squares mean difference in UPDRS motor score change from predose to 30 min postdose was −5·91 (SE 1·50, 95% CI −8·86 to −2·96) for the placebo group and −9·83 (1·51; −12·79 to −6·87) for the CVT-301 84 mg group (between-group difference −3·92 [–6·84 to −1·00]; p=0·0088). Treatments were safe and well tolerated. Severe adverse events were reported by 2 (2%) of 112 patients in the placebo group, 7 (6%) of 113 in the CVT-301 60 mg group, and 5 (4%) of 114 in the CVT-301 84 mg group, with no severe adverse event occurring in more than one patient in any treatment group. 11 (3%) of 339 patients had 19 serious adverse events (three [3%] of 112 patients in placebo, six [5%] of 113 in CVT-301 60 mg, and two [2%] of 114 in CVT-301 84 mg). Of these, hypotension and atrial fibrillation were assessed by investigators to be possibly related to the study drug. Interpretation: CVT-301 can improve UPDRS motor scores of patients with Parkinson's disease during in-clinic off periods, with few severe or serious adverse events. The long-term safety and efficacy of CVT-301 need to be investigated in future studies. Funding: Acorda Therapeutics.